Prison suicide in female detainees in Germany 2000–2013. (November 2016) - Opitz-Welke, Annette; Bennefeldt-Kersten, Katharina; Konrad, Norbert; Welke, Justus
Abstract: Specific risk factors for suicide among female prisoners were examined using an exhaustive sample of all suicides in German prisons between 2000 and 2013. The rate of prison suicide was lower among female (53, 5/100, 000) than among male prisoners (101/100, 000). Differences between the genders regarding the various risk factors for prison suicide are few. Significant differences were observed only for bullying among men and higher percentages of drug withdrawal syndrome among women. Factors specific to the prison setting that contribute to suicide risk in incarcerated women should be examined. Highlights: Suicides rates of prisoners were more than fivefold higher than in the community. The elevated suicide rates proved even higher for women. Suicide significantly decreased for men, not so for female inmates. Risk factors suicidal ideation & psychiatric examination were higher in women. Risk factor bullying virtually nonexistent in women.